(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The present study looked at how electrolytes, hormones, and postpartum reproductive physiology were affected in black Bengal goats (BBGs) when they were fed a phthalate mixture (PHA). Materials and Methods: Twenty clinically healthy BBGs, 1–2 months pregnant, aged 6–8 months with a body weight of 10–12 kg, were chosen and randomly allocated to two experimental groups (n = 10 each). The BBGs of the treatment group (n = 10) were administered a standard ration containing a mixture of Diethyl Phthalate, Dibutyl Phthalate, Di-isobutyl Phthalate, and Dipropyl Phthalate phthalate. The non-treated control group (n = 10) received the goat ration without any phthalates up to parturition. Blood samples were taken from experimental pregnant goats just before parturition to analyze serum hormone and electrolyte levels. Results: The levels of sodium, chloride, and calcium were reduced (p < 0.05) in PHA-exposed goats than in the non-exposed control group. No significant difference was observed in potassium and phosphorus levels between the two groups. PHA-exposed goats showed significantly decreased levels of estrogen, progesterone, luteinizing hormone, and thyroxin compared to control goats (p < 0.05). Postpartum reproductive traits, such as gestation length, postpartum heat period, abortion rate, and retained placenta, were significantly (p < 0.05) prolonged in BBG that had been exposed to PHA. Conclusion: PHA plasticizer exposure during pregnancy affects the electrolytes, hormones, and postpartum reproductive physiology of BBGs. J. Adv. Vet. Anim. Res., 11(4): 1050–1056, December 2024 http://doi.org/10.5455/javar.2024.k856